Estudio de factibilidad para la creación de una empresa de producción y comercialización de frutas deshidratadas, en la ciudad de Quevedo, año 2014 - Alvarez Rosado, Deny Reinaldo (2015)
This project´s aim is to know how a companies productivity and commercial dehydration of fresh fruits is created; because as time goes by companies are already evolved in turn to developing new tools, mechanisms and strategies that complement the needs of consumers and equally by those same factors, financial profitability increases in the general framework of the competitive system. The company´s feasibility was checked by different calculations in the economic-financial study, which let to know what is the quantity of the investment to start the activities $ 172,828.35 USD, which equals sum of investment and working capital. It is known that 81.18% of the capital needed will be financed through a loan from private banks and while 18.82% will be financed by equity partners of the company. Having analyzed the ratios of financial valves of the project, resulting in the NPV (net present value) is $ 361,413.35 while the IRR (internal rate of return) with a 64.03% rate higher than the interest market, so we can say that IRR> 0 then the creation of producing and marketing of a dehydrated fruit company in the city of Quevedo is feasible. The financial viability of the project is determined by an analysis of the variables that prescribe long-term profitability and simultaneously stimulates the implementation; achieving thus an effectively development socio-economic with in the city of Quevedo and the region. Moreover the economic and social investment will contribute to improving the lifestyles of people living in the community space where the company is located, acquiring sustenance and sustainability for all.